Investigation of electrical noise signal triggered resistive switching and its implications - Sun, Jianxun (2021)
In this article, the electrical noise signal triggered switching of resistive random access memory (RRAM) device is investigated. As noise is also generated when powering up the light source, such a phenomenon can be easily mistaken as a light-activated event. Thus, it is necessary to conduct a 'dark test' on the light-related experimental work to make a correct judgment of the observation. Although noise is often undesirable, we show that the voltage amplitude of the noise signal which triggers the forming process is much lower than the unipolar pulse height owing to the facilitation effect of the negative voltage. As a result, we propose a novel bipolar pulse writing scheme to reduce the forming voltage and variability. Conversely, the reverse effect is demonstrated for the set process, as the role of the negative voltage changes with the state of the device. This study provides a guideline for the design and optimization of the operation signals of the RRAM devices.